The great company (1667-1871) [electronic resource] : being a history of the Honorable Company of Merchants-Adventurers Trading into Hudson's Bay : compiled from the Company's archives; from diplomatic documents and state papers of France and England; from the narratives of factors and traders; and from many accounts and memoirs - Willson, Beckles, 1869-1942 (Toronto : Copp, Clark, 1900)
Part of a CIHM set. For individual microfiches in this set see CIHM microfiche nos. 37688-37690. Map wanting. "Vol. I." Includes bibliographical references. Electronic reproduction. Mode of access: Internet. 44